Hubungan Kontrol Diri dengan Perilaku Konsumtif Perspektif Islam (Studi pada Penggemar K-pop di Kalangan Mahasiswa Progam Studi Ekonomi Syariah Universitas Mulawarman): Penelitian - Mursyidah Nursitta Ilmina; Swadia Gandhi Mahardika; Akbar Lufi Zulfikar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
His research was conducted by Mursyidah Nursitta Ilmina with the title “The Relationship Between Self-Control and Consumptive Behavior from an Islamic Perspective (A Study on K-Pop Fans Among Students of the Sharia Economics Study Program at Universitas Mulawarman)” under the supervision by Mr. Swadia Gandhi Mahardika. The phenomenon of consumptive behavior among university students, particularly those who are fans of popular culture such as K-Pop, has become a relevant issue in the study of Islamic economics. This research aims to determine the relationship between self-control and the consumptive behavior of K-Pop fan students. This study uses a quantitative approach with a population consisting of 46 students from the Sharia Economics Study Program at Universitas Mulawarman who are K-Pop fans. Data were analyzed using linear regression analysis. The results of the study show that self-control has a negative and significant effect on students' consumptive behavior. The higher an individual's level of self-control, the lower their tendency to engage in consumptive behavior, especially toward K-Pop-related products.